CROP YIELD UNDER DIFFERENT RATES OF LIQUID DAIRY CATTLE MANURE AND MINERAL FERTILIZER - PAULETTI, Volnei; BARCELLOS, Milena; MOTTA, Antonio Carlos Vargas; MONTE SERRAT, Beatriz; SANTOS, Ivo Rodrigues dos (Scientia Agraria, 2008)
The Paraná has the fifth large dairy cattle herd among the Brazilians States, generating high volume of liquid manure. However, there is lack of long term experiments in order to establish manure rate limits for row crops fertilization at the State. A research fields were conducted on a Haplohumox soil in Castro, Paraná State, from 1997 to 2003. The study aimed to determine the summer and winter crop yields response to different liquid dairy manure rates (0, 15, 30, 45 m3 ha-1) combined with fractions of starter fertilization recommended for grain (0, 50 and 100%). The crop rotation used was soybean/black-oat/corn/wheat/dry-bean/white-oat, under no-tillage. The soybean, dry-bean, corn and wheat grain yields were not affected by starter fertilization, but the residual of this fertilization enhanced the dry matter production of black-oat and white-oat. There was no response to manure application for soybean and for black-oat dry matter. When was improve on yield by manure application, reaching maximum grain yield was obtained with 28 m3 ha-1 to dry-beans and 44 m3 ha-1 to corn and the maximum dry matter for white-oat was obtained with 41 m3 ha-1. Manure application also provided linear yield increment for wheat.